Tunggakan Dana Bagi Hasil di Provinsi Lampung dan Dampaknya terhadap Pemerintahan Daerah dalam Perspektif Sosiologi Politik - Berchah Pitoewas; Abdul Halim; Rejeki Charistias Siregar; Ririn Izzati Pangestuti; Maelinda Destriana; Putri Cahya Negara; Adinda Armilia Putri; M. Fathurrozak (CV. ITTC INDONESIA, 2025)
This study discusses the problem of Revenue Sharing Fund (DBH) arrears by the Lampung Provincial Government to the district/city government. The main focus is on the analysis of the causes of the delay in DBH payments and their impact on the performance of local government, especially in the context of political sociology. This study uses a descriptive qualitative approach with the aim of gaining a deep understanding of the causes of Revenue Sharing Fund (DBH) arrears by the Lampung Provincial Government and their impact on the local government system, especially in the context of political sociology. This study uses a literature study that collects data and information from written sources such as books, scientific articles, journals, and other published materials. The author found that the delay in DBH disbursement was caused by budget inconsistencies, accumulation of arrears since previous years, and gradual payment arrangements until 2028. The impact of DBH delays is very significant on budget realization, including delays in routine spending and infrastructure development at the district/city level. From a political sociology perspective, this reflects the unequal power relations between the provincial government and smaller regions, and shows weak fiscal transparency and accountability. More transparent and fair fiscal policy and governance reforms are needed to support the effectiveness of regional autonomy.